Answer:
x=7, -2.
Step-by-step explanation:
x^2-5x=14
x^2-5x-14=0
factor out the trinomial,
(x-7)(x+2)=0
zero property,
x-7=0, x+2=0,
x=0+7=7,
x=0-2=-2
No i don't but if u need anything else about this syndrome feel free to ask
I think you need to retype this one. The formatting makes this question difficult to understand.
Answer:
Point A:
(3, -5)
Point B:
(6, -2)
Point C:
(5, -7)
Step-by-step explanation:
Background:
Moving to the right means adding to the x.
Moving to the left means subtracting from the x.
Moving up means adding to the y.
Moving down means subtracting from the y.
So take each point and add 3 to the x, and subtract 4 from they y.
Point B:
(3, 2) → (6, -2)
Point A:
(0, -1) → (3, -5)
Point C:
(2, -3) → (5, -7)
Answer: x=-2
Y= -20
Step-by-step explanation
You replace the y in the second equation with 10x. This is because it says 10x=y
2x+10x=12x so you put that
12x=-24
To get x by its self you divide by 12.
-24 divided by 12 is -2.
Now you plug in -2 to either equation as y. I chose the first one because it's easier.
10(-2)=y
-20=y